Jawabanmu

2014-03-18T19:55:26+07:00
A. (2p + 6) x 16  = 18
            2
      32p + 96      = 18
            2
      32p + 96       = 18 x 2
      32p               = 18 x 2 - 96
      32p               = - 60
      p                   = - 60 : 32
                           =  - 1.920
B. 4x + 2 + 6        >  2 + 3x + 2 
           4                         2
     4x + 2 + 6 x 2  > 2 + 3x + 2 x 4
     8x + 4 + 12      > 8 + 12x + 8
     8x - 12x           > 8 + 8 - 4 - 12
     - 4x                 > 0
     x                     < 0 : - 4
     x                     < 0